2019
DOI: 10.1177/0885328219886953
|View full text |Cite
|
Sign up to set email alerts
|

Functionally modified magnetic nanoparticles for effective siRNA delivery to prostate cancer cells in vitro

Abstract: Different types of siRNA delivery vehicles including nanoparticles have been synthesized and utilized for prostate cancer gene therapy. However, one of the most common limitations being faced is the toxicity of cationic polymers toward the cells. In the current study, magnetic nanoparticles were prepared and conjugated with cationic polymer, polyethylenimine. Then polyethylene glycol was conjugated with polyethylenimine to improve the biocompatibility of nanoparticles. The transmission electron microscopy size… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 42 publications
1
11
0
Order By: Relevance
“…Research revealed that knockdown of both RelA (also known as nuclear factor NFκB p65 subunit) and SRF by specific siRNAs through a non-virally modified cyclodextrin vector causes significant reductions in the invasion potential of the highly metastatic PC-3 cells, partly due to the reduction of MMP-9 [91]. Similar results in terms of a decrease in cell viability of PC-3 cells were achieved through a delivery of siRNAs targeting disintegrin and metalloproteinase 10 (ADAM10) by polyethylene glycolpolyethylenimine-Fe3O4 nanoparticles [92]. Furthermore, Choi et al [93] discovered that gene silence of Bcl-2, survivin, and androgen receptor with siRNAs, which are encapsulated in pluronic F-68 polymer, along with treatment with benzethonium chloride, triggers apoptosis of human PCa LNCaP-LN3 cells more efficiently in comparison with the silencing of individual gene, suggesting that multiple gene-targeting siRNA/drug delivery system could be a feasible and promising way to Owing to their unique and easy modification properties, dendrimers have emerged as a promising system for gene/drug delivery in cancer therapy [81,82].…”
Section: Targeted Sirna Deliverymentioning
confidence: 78%
“…Research revealed that knockdown of both RelA (also known as nuclear factor NFκB p65 subunit) and SRF by specific siRNAs through a non-virally modified cyclodextrin vector causes significant reductions in the invasion potential of the highly metastatic PC-3 cells, partly due to the reduction of MMP-9 [91]. Similar results in terms of a decrease in cell viability of PC-3 cells were achieved through a delivery of siRNAs targeting disintegrin and metalloproteinase 10 (ADAM10) by polyethylene glycolpolyethylenimine-Fe3O4 nanoparticles [92]. Furthermore, Choi et al [93] discovered that gene silence of Bcl-2, survivin, and androgen receptor with siRNAs, which are encapsulated in pluronic F-68 polymer, along with treatment with benzethonium chloride, triggers apoptosis of human PCa LNCaP-LN3 cells more efficiently in comparison with the silencing of individual gene, suggesting that multiple gene-targeting siRNA/drug delivery system could be a feasible and promising way to Owing to their unique and easy modification properties, dendrimers have emerged as a promising system for gene/drug delivery in cancer therapy [81,82].…”
Section: Targeted Sirna Deliverymentioning
confidence: 78%
“…123 Panday et al designed iron oxide magnetic NCs (Fe 3 O 4 ) encapsulating PEI−PEG and loaded with disintegrin and metalloproteinase 10 (ADAM10) siRNA and released into the PC-3 cell line resulting in better cellular uptake and good biocompatibility to treat prostate cancer. 124 With a high transfection efficiency, the polycations PEI with a molecular weight of 25 kDa form polyplexes with the gene. However, the in vivo applications are constrained by the remarkable cytotoxicity and high positive charge.…”
Section: Different Types Of Ncs Used To Deliver Therapeutic Sirna And...mentioning
confidence: 99%
“…The utilization of magnetic nanoparticles is commonly adopted for siRNA delivery systems. Recently, Fe 3 O 4 nanoparticles have been developed to deliver siRNA targeting metalloproteinase 10 (ADAM10) [97] in PC cells. ADAM10 is a secreted metalloproteinase involved in various physiological processes and in tumorigenesis.…”
Section: Other Delivery Approachesmentioning
confidence: 99%